2017
DOI: 10.1111/ecog.03462
|View full text |Cite
|
Sign up to set email alerts
|

Extinction‐driven changes in frugivore communities on oceanic islands

Abstract: Global change and human expansion have resulted in many species extinctions worldwide, but the geographic variation and determinants of extinction risk in particular guilds still remain little explored. Here, we quantified insular extinctions of frugivorous vertebrates (including birds, mammals and reptiles) across 74 tropical and subtropical oceanic islands within 20 archipelagos worldwide and investigated extinction in relation to island characteristics (island area, isolation, elevation and climate) and spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 56 publications
1
76
0
Order By: Relevance
“…More comparison between insular and continental assemblages would help to understand what makes island assemblages so unique. In addition, because species traits can influence extinction risk (Heinen, van Loon, Hansen, & Kissling, 2017), using a species-based approach to evaluate non-random extinctions is also important for conservation science (Sobral, Lees, & Cianciaruso, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…More comparison between insular and continental assemblages would help to understand what makes island assemblages so unique. In addition, because species traits can influence extinction risk (Heinen, van Loon, Hansen, & Kissling, 2017), using a species-based approach to evaluate non-random extinctions is also important for conservation science (Sobral, Lees, & Cianciaruso, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we aimed to quantify pollen transport by all lava lizard species, except one which has been recently discovered (M. barringtonensis on Santa Fe island), on the main Galápagos Islands. Studies on plant-animal interactions at an archipelago scale (despite being scarce) are essential to identify key ecological links and drivers of functional shifts in insular biodiversity (Traveset et al 2015;Heinen et al 2018;Hervías-Parejo et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Seed dispersal is of vital importance in the maintenance of the structure and function of plant communities but it is also one of the most disrupted processes in habitats that have been disturbed and fragmented (Burns, ; Emer et al., ; McConkey et al., ; Neuschulz, Brown, & Farwig, ). Several studies have reported that forest fragmentation can cause a rapid extinction of animal species (Hagen et al., ), especially large‐bodied animals (Dirzo et al., ; Heinen, van Loon, Hansen, & Kissling, ). Large‐bodied mammals and birds are critical for the maintenance of intact plant communities because they contribute to the efficient seed dispersal of large‐seeded plants and help to mitigate the impact of negative density dependence (Caughlin et al., ).…”
Section: Introductionmentioning
confidence: 99%